Intrathecal pemetrexed chemotherapy combined with systemic therapy in patients with non-small cell lung cancer and leptomeningeal metastases: a retrospective study - Wenjuan Zhong; Wenjuan Zhong; Longqiu Wu; Longqiu Wu; Zhengang Qiu; Zhengang Qiu; Wei Yu; Linfang Liu; Huaqiu Shi; Huaqiu Shi; Shugui Wu (Frontiers in Oncology)
BackgroundLeptomeningeal metastases (LM) in non-small cell lung cancer (NSCLC) present a challenging prognosis, with systemic therapies often limited by the blood-brain barrier. However, intrathecal pemetrexed injections can increase intracranial drug concentrations, aiding in disease control.ObjectiveTo evaluate the efficacy and safety of combining intrathecal pemetrexed with systemic therapy in patients with NSCLC and LM.MethodsThirty-one patients with NSCLC and LM who received intrathecal pemetrexed chemotherapy between 2018 and 2022 at First Affiliated Hospital of Gannan Medical College were retrospectively reviewed.ResultsOf the 31 patients enrolled, six had LM at initial diagnosis. The median number of intrathecal pemetrexed injections was 4 (2-26), with an intracranial control rate of 87.1% (27/31). Median iPFS was 9 months (95% CI: 2.77-15.23), and median iOS was 12 months (95% CI: 5.94-18.06 months). Most adverse events (AEs) were grade 1-2, with four (12.9%) grade 3 AEs (including two cases of grade 3 leukopenia; one, grade 3 diarrhea; one, grade 3 interstitial pneumonitis). Univariate and multivariate analyses showed that the combination of bevacizumab (p<0.05) and an Eastern Cooperative Oncology Group(ECOG) score of ≤ 1 (p<0.05) were favorable prognostic factors for survival.ConclusionIntrathecal pemetrexed injections combined with systemic treatment demonstrated significant therapeutic efficacy and manageable safety in NSCLC patients with LM.